Peran Hukum Pidana dalam Perlindungan Data Pribadi dan Pencegahan Kejahatan Siber di Indonesia - Ahmad Sauki Warouw (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The rapid development of digital technology has increased the risk of privacy violations and cybercrimes targeting personal data. This study aims to analyze the role of criminal law in personal data protection and the prevention of cybercrimes in Indonesia, as well as to identify the challenges and strategies for strengthening law enforcement in the digital era. The research method used is a qualitative approach with a juridical-normative method through library research on regulations, particularly Law Number 27 of 2022 concerning Personal Data Protection (PDP Law), as well as related academic literature. The results of the study show that criminal law serves a dual function, acting as a repressive tool through the imposition of criminal sanctions on offenders, and as a preventive instrument in enhancing compliance with data security standards. Although the PDP Law provides a strong legal foundation, its implementation still faces challenges such as the suboptimal functioning of data protection institutions, limited capacity of law enforcement officers, and low public awareness of digital ethics. This study recommends institutional strengthening, enhancement of law enforcement human resource capacity, as well as public education and cross-sectoral synergy to create an effective and sustainable data protection system. Thus, criminal law plays a central role in safeguarding personal data and preventing cybercrimes in Indonesia.